ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH TERHADAP KPR PADA PT BNI CABANG TANJUNG REDEB - Djupiansyah Ganie (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
Customers 'interest in owning a house through a KPR, apart from the urge to fulfill their need for a comfortable and nice place to live, is also related to how the KPR is marketed so that it attracts customers' interest. Or in other words, how is the marketing mix strategy implemented to attract buyers to the mortgage offered. The marketing mix includes products, prices, promotions, locations, people, processes and physical evidence.The purpose of this study was to determine the influence of factors including: product, price, promotion, location, people, process and physical evidence on customer interest in KPR at PT BNI TanjungRedeb Branch. The research data comes from a questionnaire distributed to 86 respondents who are KPR BNI Griya customers, using probability sampling method with simple random sampling technique. The analytical tool used is the validity test, reliability test, multiple linear regression, coefficient of determination, t test and F test.The results of this study indicate that the results of the t test on each research variable concluded that partially accepting the hypothesis point 1 and rejecting some of the hypothesis point 1, because it is proven that the location factor has a significant influence, while the product, price, promotion, people, process and Physical evidence does not have a significant effect on customer interest in the KPR PT BNI TanjungRedeb Branch. The results of the F test on all the variables studied conclude that accepting the hypothesis point 2, because it is proven that the factors which include: product, price, promotion, location, people, process and physical evidence together have a significant influence on customer interest in KPR PT BNI TanjungRedeb Branch